2013
DOI: 10.1159/000353192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Alginate on Dextran Sulfate Sodium- and 2,4,6-Trinitrobenzene Sulfonic Acid-Induced Experimental Colitis in Mice

Abstract: We evaluated the effects of sodium alginate (AL-Na) on dextran sulfate sodium (DSS)- and 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis in mice. DSS was added to the drinking water for 7 days. In another experiment, DSS was added to the drinking water for 5 days and DSS-free water was provided thereafter. In a separated study, colitis was induced by intrarectally administered TNBS. AL-Na, 5-aminosalicylic acid, or prednisolone was orally administered. These colitis models exhibited colonic damage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…In this way, sodium alginate could suppress indomethacin-induced SII in mice. In agreement with this hypothesis, HMW sodium alginate has been shown to improve inflammation in the lower GIT in an experimental model of colitis 15 , 22 and in methotrexate-induced SII 16 . Here, we also showed that, in addition to HMW sodium alginate, pretreatment with LMW sodium alginate ameliorated indomethacin-induced SII in mice.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In this way, sodium alginate could suppress indomethacin-induced SII in mice. In agreement with this hypothesis, HMW sodium alginate has been shown to improve inflammation in the lower GIT in an experimental model of colitis 15 , 22 and in methotrexate-induced SII 16 . Here, we also showed that, in addition to HMW sodium alginate, pretreatment with LMW sodium alginate ameliorated indomethacin-induced SII in mice.…”
Section: Discussionsupporting
confidence: 58%
“…Sodium alginate is a soluble dietary fiber extracted from brown seaweed. It is a heteropolymer of D-mannuronic acid and L-guluronic acid 15 . The molecular weight of sodium alginate depends on by hydrolysis condition in its production.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we cannot disregard the possibility that alginate composition is important in the potency of anti-inflammatory effects. 30 Hyaluronic acid, another protective solution used in clinical practice, has been recognized as an adjuvant therapy for inflammatory diseases involving the upper aerodigestive tract. There are both basic and clinical research studies to elucidate the anti-inflammatory mechanisms initiated by hyaluronic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium alginate (SA) is a heteropolymer of d -mannuronic acid and l -guluronic acid. It is a soluble dietary fiber extracted from brown algae [8]. SA is in widespread clinical use as a hemostatic agent to treat gastrointestinal tract (GIT) bleeding caused by gastric and duodenal ulcers, erosion of the gastric mucosa, or reflux esophagitis [9].…”
Section: Introductionmentioning
confidence: 99%
“…SA is in widespread clinical use as a hemostatic agent to treat gastrointestinal tract (GIT) bleeding caused by gastric and duodenal ulcers, erosion of the gastric mucosa, or reflux esophagitis [9]. SA has been reported to reduce mucosal damage and inflammation in animal models of inflammatory bowel disease [8].…”
Section: Introductionmentioning
confidence: 99%